(untitled) (International Journal of Food and Nutritional Sciences, 2022)
War is a clash between armed forces between two nations or two different groups have difference of opinion in a particular affair. War creates great destructions. Millions of lives get destroyed during the war. War can be evaded by humanity or compassion. Hence, War is not climax to any issues. The two novels of Richard Flanagan explores how the lives of people shatters amidst the war and their survival throughout the war period. War kills, destroys and ruins the lives, the government,the nation, the world and so on . War victims would move to other countries and they lead their life as refugees. “The Sound of One Hand Clapping and The Narrow Road to the Deep North” are the two novels chosen for this article.